(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract . The study of bone fractures in dogs due to various causes, their correction with various surgical methods, the study of differences in the time of bone healing in dogs of different ages, the preparation of dogs before surgery and the care of dogs after surgery, the analysis of literature data and scientific research based on them were conducted. Experimental, comparative, microscopic, surgical examination methods were widely used in this. Based on the data obtained, new methods were used to organize modern measures for the treatment of the disease.